1970
DOI: 10.1159/000152304
|View full text |Cite
|
Sign up to set email alerts
|

The Genetical Interpretation of Haemoglobin H Disease

Abstract: The clinical and haematological data of nine patients with haemoglobin H disease, as well as of 16 members of their families, are reported. Pedigree study and haematological data permit the assumption that in an individual four genes could be responsible for α-chain synthesis. Based on this hypothesis, four variants of α-thalassaemia are expected to exist. The first, in which only one gene is affected has no, or only minor, red cell changes and an increase in Hb Bart’s at birth, the second with two genes affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1970
1970
1977
1977

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Genetic evidence suggests that HbH disease results from the interac tion of two a-genes, although whether allelic, closely linked or segregating independently, it is still not clear [7,14]; it is also suggested that three ab normal genes may be involved and HbH disease results when two are pre sent, severity and symptoms depending on the type of gene combination [8]; or that, from one to four genes of the a-thalassaemic type may be in volved, with progressive effects -minimal with one, more pronounced with two, HbH disease with three, and Bart's hydrops with all four [6], The case reported here showed no slow-moving Hb fraction, and is likely to be of the a-thalassaemia-1, 2 doubly-heterozygous type, although there are no family studies to support this. The findings on the blood of the pa tient's husband and baby also do not completely exclude the presence of a minimally expressed a-thalassaemia trait in either.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic evidence suggests that HbH disease results from the interac tion of two a-genes, although whether allelic, closely linked or segregating independently, it is still not clear [7,14]; it is also suggested that three ab normal genes may be involved and HbH disease results when two are pre sent, severity and symptoms depending on the type of gene combination [8]; or that, from one to four genes of the a-thalassaemic type may be in volved, with progressive effects -minimal with one, more pronounced with two, HbH disease with three, and Bart's hydrops with all four [6], The case reported here showed no slow-moving Hb fraction, and is likely to be of the a-thalassaemia-1, 2 doubly-heterozygous type, although there are no family studies to support this. The findings on the blood of the pa tient's husband and baby also do not completely exclude the presence of a minimally expressed a-thalassaemia trait in either.…”
Section: Discussionmentioning
confidence: 99%
“…gene produces 5% Hb Barts in newborns, whereas the presence of one «-thal2 produces levels of approximately 1 -2 % . Another interpreta tion, based on the duplication of the «-chain locus, which also explains the different types of «-thalassaemia, has been proposed by Kattamis and Lehmann [2], According to this model, the inactivity of one, 2,3 or of all the 4 a-genes is responsible for the various types of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, one person could possess 1 to 4 «-thalassaemia genes, which would explain the vari ability in the expression of «-thalassaemia. Kattamis and Lehmann [7] thought that clinical and haematological findings could be classified by the number of «-genes involved: minimal changes when 1 gene is pres ent, more pronounced changes when 2 genes are abnormal, Hb H dis ease when 3 genes are present, and hydrops foetalis when all 4 genes are abnormal. This theory sounds very attractive, especially since Brimhall et al [1] have presented evidence for the presence of 2 a-chain genes in man.…”
Section: Discussionmentioning
confidence: 99%